One-week 96-well soft agar growth assay for cancer target validation - Ning Ke; Aaron Albers; Gisela Claassen; De-hua Yu; Jon E. Chatterton; Xiuyuan Hu; Bernd Meyhack; Flossie Wong-Staal; Qi-Xiang Li (BioTechniques)
Soft agar growth, used to measure cell anchorage-independent proliferation potential, is one of the most important and most commonly used assays to detect cell transformation. However, the traditional soft agar assay is time-consuming, labor-intensive, and plagued with inconsistencies due to individual subjectivity. It does not, therefore, meet the increasing demands of today's oncology drug target screening or validation processes. This report describes an alternative 96-well soft agar growth assay that can function as a replacement for the traditional method and overcomes the aforementioned limitations. It offers the following advantages: a shortened assay duration (1 week instead of 4 weeks) that makes transient transfection or treatment possible; plate reader quantification of soft agar growth (measuring cloning efficiency and colony size); and a significant reduction in required labor. Higher throughput also makes it possible to process large numbers of samples and treatments simultaneously and in a much more efficient manner, while saving precious workspace and overall cost.